Private sector participation in agricultural research and development. Notes on issues and concerns - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
Some of the main forces behind the growth of the private sector in agricultural technology research and development are reviewed, finally the concerns and problems arising from the new institutional situation are discussed.